REFLEXIVITY, INTENTIONALITY, AND THE EMBODIED SUBJECT: A PHENOMENOLOGICAL REFLECTION IN HONOR OF J. N. MOHANTY. - MacKenzie, Matthew (Philosophy East & West: A Quarterly of Comparative Philosophy, 2025)
The article focuses on understanding the relationship between reflexivity, intentionality, and embodiment in consciousness through a phenomenological lens, in dialogue with both classical Indian and Western philosophical traditions. Topics include the interdependence of reflexivity and intentionality, models of consciousness in Indian philosophies such as Nyāya, Advaita, and Buddhist pramāṇavāda, and the role of the embodied subject as the locus of conscious life.